2006
DOI: 10.1039/b607180e
|View full text |Cite
|
Sign up to set email alerts
|

Photocleavable peptide hydrogel arrays for MALDI-TOF analysis of kinase activity

Abstract: We have developed an acrylamide copolymerization strategy to immobilize acrylamide labeled peptides and proteins into a hydrogel surface and detect their modifications using MALDI-TOF mass spectrometry. Copolymerization into hydrogels is robust, compatible with "off-the-shelf" chemistry, and yields materials and surfaces that are stable to aqueous or organic solvents, drying, high or low temperature, high or low pH, oxidizing agents, sonication, mechanical contact, etc. The use of acrylamide hydrogels allows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Similarly, substrates that included p40 were phosphorylated more rapidly than Abltide alone (Figure 3D). Mass spectrometry and fluorescent anti-phosphotyrosine antibody labeling confirmed that signal increases were not the result of phosphorylation at an additional tyrosine in p40 (17, 36). Results from these competition assays suggested that p40 recruits Bcr-Abl to the bead surface by interaction with the SH3 domain.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, substrates that included p40 were phosphorylated more rapidly than Abltide alone (Figure 3D). Mass spectrometry and fluorescent anti-phosphotyrosine antibody labeling confirmed that signal increases were not the result of phosphorylation at an additional tyrosine in p40 (17, 36). Results from these competition assays suggested that p40 recruits Bcr-Abl to the bead surface by interaction with the SH3 domain.…”
Section: Resultsmentioning
confidence: 82%
“…Previous work using immobilized Abltide to measure Bcr-Abl activity in cell lysates demonstrated that altered orientations resulted in increased signal intensities (35). It was also shown that inclusion of p40, the high-affinity peptide ligand for the Abl kinase SH3 domain, led to more efficient phosphorylation of Abltide (17, 36). To test the influence of peptide orientation on assay sensitivity we synthesized Abltide with a carboxyl-terminal cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was also adopted by Parker et al (2006); here, acrylamide-labeled peptides were immobilized in a hydrogel surface and the enzymatic activity of a kinase was studied by detecting the phosphorylated peptides (Fig. 15).…”
Section: Plate With An Enzyme or Substrates Bound To Its Surfacementioning
confidence: 99%
“…15). Cleavage of peptides from the plate was performed directly using the MALDI laser, or by treatment with an auxiliary UV light source, and the matrix added subsequently to enable detection by MALDI-MS (Parker et al, 2006). Yet another protocol for immobilization of substrates of an enzyme was demonstrated by Mrksich and co-workers who implemented SAMDI-MS.…”
Section: Plate With An Enzyme or Substrates Bound To Its Surfacementioning
confidence: 99%
“…Regioselective immobilisation of poly(desoxythymidin)-modified kinase substrates onto differently coated glass slides was reported for PKA and c-Src [49]. Photocleavable acrylamide labelled cysteine-containing kinase substrates were incorporated into peptide-acrylamide copolymer hydrogel surfaces and v-Abl-or c-Abl-mediated phosphorylation was detected by MALDI-TOF/TOF subsequent to laser-induced cleavage at the ß-(2-Nitrophenyl)-ß-alanine residue [50]. There are several additional chemistries used for the chemoselective immobilisation of peptides onto different surfaces (comprehensively reviewed in [19]) like formation of covalent bonds by reaction of salicylhydroxamic acids with 1,3-phenyldiboronic acid derivatives [51][52][53] or semicarbazides with aldehydes [54][55][56][57][58][59][60] or using thio-ene chemistry [61][62][63][64] but no applications for enzyme profiling have been described so far.…”
Section: Chemistry Of Peptide Array Preparationmentioning
confidence: 99%